The effect of tuition fee reduction and education subsidy on school enrollment: Evidence from Vietnam. (January 2020) - Bui, Tuan Anh; Nguyen, Cuong Viet; Nguyen, Khuong Duc; Nguyen, Ha Hong; Pham, Phuong Thu
Highlights: We examine the impact of public policy on the children's enrollment rate in Vietnam. We find significant impacts of the tuition fee reduction and education subsidy. The school enrollment rate of beneficiary children is 5 percentage points higher. The effect is stronger for poor and ethnic minority children. Abstract: This paper examines the impact of two education incentive policies including tuition fee reduction and education subsidy on secondary-school enrollment of children in Vietnam. Using Vietnam Household Living Standard Surveys during the 2006–2018 period, we find that both policies significantly increase the school enrollment rate of children. The effect of these policies varies across different groups of children with a greater effect on those from ethnic minority groups, rural areas, poor and low-income households. Our findings suggest that these education incentive programs are an effective way to encourage children to enroll school, especially in low- and middle-income countries.